Czech philosophy in the life of the nation at the end of the 19th centuries - Zouhar, Jan (Folia Philosophica, 2001)
The paper deals with the situation in the Czech philosophy at the break of 19th and 20th centuries considered on the background of the social-national and political life of the Czech nation, considerations over that situation have been carried out in three aspects: 1) the relation of Czech philosophy to European philosophy; 2) the crisis of philosophy and, generally, the social crisis and the crisis in which man has found himself; 3) practical-utilitarian character of the Czech philosophy. In the first case, despite some unfavourable opinions about Czech philosophical thinking, the activity of Czech philosophers at that time was significant - the periodical „Česka mysl” begins to appear as well as works relating to main European philosophical currents. In the second aspect - the crisis concerns the historical conditioning of the reflection on the situation which is connected with a kind of impatience. The totality of culture was submerged in the atmosphere of the end of the century, revaluation of values, the beginning of Modernism. The consciousness of the crisis determined the individual expressions of the authors, it became their basic point of reference. In the third case the Czech philosophy, though with exceptions, looms as the so called marginal philosophy, as applied philosophy connected with some historical situation, interpreting that situation and reacting to the practical problems and their solving, as a philosophy which deals with questions considered to be socially current. In the works of the philosophers there showed itself one of the permanent features of the Czech philosophical thinking which is connected with the life activities, with everyday life. It was acknowledged because it proved the ability to solve practical problems and to answer the vital questions of our national and individual lives.